The Effect of Sutureless Surgery on Postoperative Pain and Swelling Following Mandibular Third Molar Surgery - Mozhgan Kazemian; Majid Eshghpour; Sina Ilkhani; Nafise Ghadirimoghaddam (Mashhad University of Medical Sciences, 2016)
Introduction: surgeons have always sought to use techniques to decrease pain and swelling. One of the solutions that can minimize these complications is closing the wound with the minimum number of sutures or sutureless technique. The goal of this study was to evaluate the role of sutureless technique in decreasing pain and swelling after impacted mandibular third molar surgery. Methods: nineteen patients with bilaterally mandibular impacted third molars (one side as control and the other as the case) entered the study. A single surgeon performed the surgery using a single protocol. After removing each tooth, the flap on the control side was sutured, while on the study side, it was handled sutureless. Post-operative pain evaluated with visual analogue scale (VAS) at first, third and seventh days after surgery. Inflammation evaluated with measuring the distance between tragus and oral commissure in the same distance. Result: In our study, in all patients, the average mean pain score increased from the first to the third day and decreased from third to seventh day and the difference in the average of pain scores in the aforementioned three days was significantly different(p